Implantación de un sistema contable en el micromercado Celi Celi, del cantón Catamayo, provincia de Loja, periodo: agosto a septiembre del 2014 - Celi Celi, Tatiana Elizabeth (2015)
This thesis entitled IMPLEMENTATION OF AN ACCOUNTING SYSTEM IN THE MICROMARKET CELI CELI, THE CANTON CATAMAYO, PROVINCEOFLOJA,PERIOD:AUGUSTSEPTEMBER2014,allowed implement the knowledge acquired during the years of study at the career of Accounting and Auditing complying with the necessary requirements for the degree of Engineer in Accounting and Auditing, Public Auditor- Accountant. This subject is aimed at obtaining adequate and timely financialstatements. The proposed objectives were fully met especially with the introduction of commercial accounting, this is what made in order to have a proper financial accounting and timely procedure being one of the main objectives of the research. It could make by organizing documents, preparation of the Initial Inventory based on physical verification of the merchandise and supporting documentation; likewise Plan was developed and User accounts, auxiliary registers, providing income support costs registration information in the general journal was designed. The accounting process was run from baseline to the financial statements for the period August to September2014. Upon completion of the investigation was obtained as a conclusion the development of real and timely financial statements also important to continue running the accounting process with all auxiliary records of the sale, the Kardex cards for better control of goods, depreciation assets, this so that the results are reliable in making decisions for the betterment of the company